On altruism and remittances - Alexis Antoniades; Ganesh Seshan; Roberto Weber; Robertas Zubrickas (University of Zurich, Department of Economics, 2013)
We provide a direct test of the impact of altruism on remittances. From a sample of 105 male migrant workers from Kerala, India working in Qatar, we elicit the propensity to share with others from their responses in a dictator game, and use it as a proxy for altruism. When the entire sample is considered, we find that only migrants' income robustly explains remittances. Altruism does not seem to matter. However, we document a strong positive relationship between altruism and remittances for those migrants that report a loan obligation back home, which is nearly half the sample. We explain the role of loan obligations with a standard remittance model, extended with reference-dependent preferences.
Keywords: O12; O15; D81; 330; remittances; altruism; reference-dependent preferences; dictator game; Qatar